2022
DOI: 10.1038/s41396-022-01293-w
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition and evolution of enhanced mutualism—an underappreciated mechanism for invasive success?

Abstract: Soil biota can determine plant invasiveness, yet biogeographical comparisons of microbial community composition and function across ranges are rare. We compared interactions between Conyza canadensis, a global plant invader, and arbuscular mycorrhizal (AM) fungi in 17 plant populations in each native and non-native range spanning similar climate and soil fertility gradients. We then grew seedlings in the greenhouse inoculated with AM fungi from the native range. In the field, Conyza plants were larger, more fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 92 publications
2
17
0
1
Order By: Relevance
“…We emphasize that our binary approach to herbivore diet (generalist vs. specialist) was heuristic, and thus too simplistic (Hardy et al, 2020), but appeared to have allowed us to detect some fundamental ecological phenomena. Finally, the best tests of hypotheses such as ours compare the same species in native and non-native ranges (Sheng et al, 2022), and it should be noted that studying defenserelated tradeoffs among native and non-native species in the same non-native range provides strong, but not the best, evidence for defense adaptations (Van Kleunen et al, 2010). However, including many non-native and native congeners increases the strength of our results.…”
Section: Cost-benefit Allocationmentioning
confidence: 67%
“…We emphasize that our binary approach to herbivore diet (generalist vs. specialist) was heuristic, and thus too simplistic (Hardy et al, 2020), but appeared to have allowed us to detect some fundamental ecological phenomena. Finally, the best tests of hypotheses such as ours compare the same species in native and non-native ranges (Sheng et al, 2022), and it should be noted that studying defenserelated tradeoffs among native and non-native species in the same non-native range provides strong, but not the best, evidence for defense adaptations (Van Kleunen et al, 2010). However, including many non-native and native congeners increases the strength of our results.…”
Section: Cost-benefit Allocationmentioning
confidence: 67%
“…Previous studies showed that plant-AMF interactions were either independent of invasive status (Bunn et al, 2015) or were greater (Sheng et al, 2022; or weaker (Vogelsang and Bever, 2009) in invaders than natives. In this study, we found that differences in plant-AMF interactions between S. decurrens and S. canadensis were amplified with greater P availability.…”
Section: Variations In Plant-amf Interactions Induced By Soil P Formsmentioning
confidence: 99%
“…Although there was an association between AMF diversity and plant performance, it should be noted that the non-negligible roles of certain AMF taxa on invasive plant-AMF interactions. For example, Sheng et al (2022) found that a higher abundance of Glomeraceae in non-native Conyza canadensis enhanced their growth in invasive populations to a greater extent than native populations, suggesting specific AMF taxa play important roles in influencing the invasiveness of exotic species. Our results revealed that variations in abundance of Glomeraceae, the predominant taxon in the AMF families, exhibited positive relationship with the growth advantage of S. canadensis compared with Diversisporaceae and Acaulosporaceae.…”
Section: Variations In Plant-amf Interactions Induced By Soil P Formsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kalisz et al, 2014)。然而, 越来越 多研究发现入侵地一些植食性天敌的采食行为也 可能阻抗外来植物入侵(Kempel & Chrobock et al, 2013;Schultz et al, 2017;Zhang et al, 2018;Christianen et al, 2019)。例如 ,& Vilà, 2001;Huang et al, 2010; Schaffner et al, , 2017;Mariotte et al, 2018;Zhang X et al, 2021)。菌根真菌在外来植物入侵中的作用近年 来得到了关注(Suding et al, 2013;Bunn et al, 2015;Dickie et al, 2017;Chen et al, 2020)。 "共生促进"假说 (enhanced mutualisms hypothesis)认为, 外来植物在 入侵地与当地一些高效的共生真菌形成新的相互 作 用 , 促 进 其 入 侵Baynes et al, 2012;Tian et al, 2021;Sheng et al, 2022;Yu et al, 2022)。 例 如 , 与原产地种群相比, 乌桕与小 飞蓬(Conyza canadensis)的入侵地种群的菌根真菌 寄生率更高、植物生物量更大(Yang et al, 2015;Sheng et al, 2022), 这种更强的"共生促进"关系主要 是由根系分泌物中类黄酮的变化驱动的(Tian et al, et al, 2013;Stricker et al, 2016), 也可能通过溢出效应对邻近植物产生抑制, 从而促进入侵 al, 2020b)。同理, 本地植物也会募集一些病原微生物 抑制外来植物入侵(Zhang et al, 2020a)。另外, 本地 植物募集的病原微生物对外来植物的抑制作用通 常高于外来植物募集的病原微生物对外来植物的 抑制作用(Zhang et al, 2020b), 时发生(Waller et al, 2020; Allen et al, 2021)。自 Bennett (2013)综述并强调了这种复杂多类群互作 (Liu et al, 2017), 并且这种促 进效应 在水 生系 统 更加明显 (Sorte et al, 2013)。增温(Haeuser et al, 2017, 2019) 与 大 气 CO 2 浓 度 上 升 (Blumenthal et al, 2013; Mozdzer & Caplan, 2018)驱动外来植物入侵的现象 也不断被证实。一项基于全球13个国家64片草地的 养分添加实验发现, 养分增加显著提高了外来植物 优势度(Seabloom et al, 2015)。同样, 水分和光照等 资 源 的 增 加 也 可 能 加 速 外 来 植 物 的 入 侵 过 程 (Davidson et al, 2011; Sorte et al, 2013)。最新的研究 暗示城市化进程中路灯建设引起的夜间光污染促 进了一些外来植物的入侵(Speißer et al, 2021; Liu YJ et al, 2022; Murphy et al, 2022)。另外, 与单一的 光照或养分增加相比, 光照与养分同时增加更能加 剧外来入侵植物对本地植物的竞争排斥(Zhang et al, 2022)。因此 , Richards等(2006)指出许多外来入侵植 物在应对生存条件变优越、资源增加的环境变化时 "专家型策略" (master of some)。最新的研 究显示干旱(Copeland et al, 2016; Liu et al, 2017; Valliere et al, 2019)与臭氧胁迫(Wang LC et al, 2022) Zhang et al, 2020a; Li YJ et al, 2022)。 这也解释了为 什 么 个 别 研 究 发 现 资 源 波 动 不 影 响 (Frevola & Hovick, 2019; Shi et al, 2021)甚至抑制外来植物入 侵(Liu et al, 2018), 群 落 (novel community) 或 新 型 生 态 系 统 (novel ecosystem, Richardson & Gaertner, 2013)。这 2017 年 , Journal of Ecology 发 表 了 关 于 "Long-Term Dynamics and Impacts of Plant Invasions" species role), 对传粉网络的嵌套性 (nestedness) 、 连 通 度 (connectance) 和 稳 健 性 (robustness) 等 可 能 无 显 著 影 响 (Bartomeus et al, 2008; Stouffer et al, 2014; Parra-Tabla et al, 2019; Corcos et al, 2020)。 目前, WW et al, 2020; Qiu et al, 2020; Xu et al, 2022b), 以及植食动物(Xu et al, 2022a)和致病 微生物(Li et al, 2014)等介导的间接影响, 显著改变 了我国南方红树林和中、北部盐沼生态系统的植物 群落组成与结构(Wang et al, 2019; Ren et al, 2021), 导致依赖于本地生产者为营养源或栖息生境的昆 虫(Sun KK et al, 2020)、土壤生物(Zhang YZ et al, et al, 2019), 不仅能够改变其新占据生 境的植物群落组成(Alexander et al, 2015)和地上昆 虫群落(Bezemer et al, 2014), 还可以改变这些区域 的土壤线虫群落(Wilschut et al, 2016)和微...…”
unclassified